2008
DOI: 10.1292/jvms.70.255
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Responsible for Reduced Cardiotoxicity of Mitoxantrone Compared to Doxorubicin Examined in Isolated Guinea-Pig Heart Preparations

Abstract: ABSTRACT. We reported previously that doxorubicin, an anticancer agent that has an anthracycline structure, alters Ca 2+ releasing and uptake mechanisms in the sarcoplasmic reticulum of myocardial cells. These effects of doxorubicin are apparently related to its cardiotoxicity. Mitoxantrone is a similar anticancer agent with an anthracenedion structure that has been shown to be significantly less cardiotoxic. In the present study, the effects of mitoxantrone on the functions of the sarcoplasmic reticulum were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…Mitoxantrone (MXT) is a synthetic antineoplastic drug structurally analogous to anthracyclines such as doxorubicin (DOX). MXT has been used in the treatment of various cancers including leukemia, non-Hodgkin lymphoma and breast cancer (29). To the best of our knowledge, there is no report related to the degradation of MXT by the electro-Fenton process.…”
Section: Mxt + Ohmentioning
confidence: 99%
“…Mitoxantrone (MXT) is a synthetic antineoplastic drug structurally analogous to anthracyclines such as doxorubicin (DOX). MXT has been used in the treatment of various cancers including leukemia, non-Hodgkin lymphoma and breast cancer (29). To the best of our knowledge, there is no report related to the degradation of MXT by the electro-Fenton process.…”
Section: Mxt + Ohmentioning
confidence: 99%
“…Mitoxantrone is an anthracenedione that was designed to function like an anthracycline but have less cardiotoxicity 85 because it is less likely to form free radicals 35 and may affect calcium release differently. 86 Like anthracyclines, mitoxantrone can intercalate in DNA and poison TopII to form DNA double-stranded breaks. This drug is approved for hormone-refractory prostate cancer.…”
Section: Topoisomerase I Inhibitors (Camptothecins-irinotecan Topotementioning
confidence: 99%
“…The amplitude of [ca 2+ ] i was calculated by subtraction of the value of the 340/380 nm ratio at the maximal diastolic period from the value of the 340/380 nm ratio at the peak of [ca 2+ ] i [4]. In the experiments with EGcG (20, 100, and 300 µM) and EcG (5 and 50 µM), the force of contraction and [ca 2+ ] i were examined in one muscle preparation using one concentration of each catechin.…”
Section: Animalsmentioning
confidence: 99%
“…The left atrial muscle preparation showed stable contractions during repeated electrical stimulation throughout a relatively long experiment [4]. In addition, since the muscle tissue is sufficiently thin and the size is appropriate for measurement of [ca 2+ ] i, this experiment has the advantage that simultaneous recordings of the force of contraction are possible from the same area of the myocardial tissue with only a small variation in experimental results.…”
mentioning
confidence: 99%